Development of a vessel-mimicking material for use in anatomically realistic Doppler flow phantoms - FAGAN, ANDREW JOHN (My University, 2011)
Polyvinyl alcohol cryogel, (PVA-C) is presented as a vessel mimicking material for use in anatomically realistic Doppler flow phantoms. Three different batches of 10 % wt PVA-C containing (i) PVA-C alone, (ii) PVA C with anti-bacterial agent and (iii) PVA-C with silicon carbide particles were produced, each with 1 to 6 freeze-thaw cycles. The resulting PVA-C samples were characterized acoustically (over a range 2.65 ? 10.5 MHz) and mechanically in order to determine the optimum mixture and preparation for mimicking the properties of healthy and diseased arteries found in vivo. This optimum mix was reached with the PVA-C with anti-bacterial agent sample, prepared after 2 freeze/thaw cycles, which achieved a speed of sound of 1538 ? 5 m s 1 and a Young?s elastic modulus of 79 ? 11kPa. This material was used to make a range of anatomically-realistic flow phantoms with varying degrees of stenoses, and subsequent flow experiments revealed that higher degrees of stenoses and higher velocities could be achieved without phantom rupturing compared to a phantom containing conventional wall-less vessels.
PUBLISHED
Keywords: Polyvinyl alcohol cryogel; anatomically realistic flow phantom; vessel mimic; acoustic and mechanical characterisation